Analysis of Match Performance Indicators of University Futsal Teams in the 2026 National Collegiate Futsal Series - Nisa Meliana; Jajat; ⁠Kuston Sultoni (Universitas Negeri Jakarta Postgraduate of Physical Education Departments, 2026)
This study aimed to identify match performance indicators associated with winning in university futsal teams competing in the 2026 National Collegiate Futsal Series (NCFS). A quantitative descriptive-comparative design was employed using official statistics from 410 matches across ten regional competitions, resulting in 820 team-match observations: 365 wins, 90 draws, and 365 losses. The analyzed indicators included goals scored, shots on target, shots off target, ball possession, pass accuracy, tackles, missed penalties, fouls committed, yellow cards, and red cards. Because goals scored directly determines match outcomes, it was used only as a descriptive outcome-validation indicator and was not treated as a predictor of success. Data were analyzed using descriptive statistics and the Kruskal–Wallis test, followed by Dunn–Holm post hoc comparisons. Significant differences among winning, drawing, and losing teams were found in shots on target, shots off target, ball possession, pass accuracy, fouls committed, and yellow cards (p < 0.05), although the effect sizes were generally small (ε² = 0.001–0.052). Pass accuracy and ball possession showed the largest effects. Post hoc analysis indicated that winning teams recorded significantly more shots on target, greater ball possession, and higher pass accuracy than drawing and losing teams. Descriptively, winning teams also scored more goals than drawing and losing teams. Conversely, tackles, missed penalties, and red cards did not differ significantly across match outcomes (p > 0.05). These findings suggest that attacking effectiveness and game control, particularly shot accuracy, ball possession, and passing accuracy, are the performance indicators most consistently associated with winning in university futsal.